Molecular Epidemiology and Genetic Diversity of Norovirus in Young Children in Phnom Penh, Cambodia. (27th December 2016) - Nakjarung, Kaewkanya; Bodhidatta, Ladaporn; Neesanant, Pimmnapar; Lertsethtakarn, Paphavee; Sethabutr, Orntipa; Vansith, Ket; Meng, Chhour Y.; Swierczewski, Brett E.; Mason, Carl J.
Abstract : This study investigated the genetic diversity of noroviruses identified from a previous surveillance study conducted at the National Pediatric Hospital in Phnom Penh, Cambodia, from 2004 to 2006. In the previous study, 926 stool samples were collected from children aged 3–60 months with acute diarrhea (cases) and without diarrhea (controls) with reported 6.7% of cases and 3.2% of controls being positive for norovirus. The initial norovirus diagnostic assay was performed with real-time reverse transcription-polymerase chain reaction (real-time RT PCR) which also distinguished between genogroups I and II (GI and GII). Norovirus infection was most commonly detected in children aged 12–23 months in both cases and controls. Norovirus Genotyping Tool and phylogenetic analysis of partial sequences of the 3′ end of the RNA-dependent RNA Polymerase (RdRp) and the capsid domain region were employed to assign genotypes of the norovirus strains. GII.4 was the most predominant capsid genotype detected at 39.5% followed by GII.6 at 14.9%. The GII.4 Hunter 2004 variant was the predominant strain detected. Six RdRP/capsid recombinants including GII.P7/GII.6, GII.P7/GII.14, GII.P7/GII.20, GII.P12/GII.13, GII.P17/GII.16, and GII.P21/GII.3 were also identified. This study of norovirus infection in young children in Cambodia suggests genetic diversity of norovirus as reported worldwide.